Analisis Hubungan Lama Kerja terhadap Keluhan Muskuloskeletal pada Petugas Keamanan di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Kristen Krida Wacana - Hartanto Hartanto; Ellin Benecia Salim; Riki Kartadinata; Erma Mexcorry Sumbayak; Yusuf Handoko; Elly Ingkiriwang (Jurnal Ners, 2026)
Injuries or disorders that occur in the skeletal muscle system are referred to as Musculosceletal Disorders (MSDs). Musculoskeletal disorders can occur due to an imbalance of activity loads on the capabilities of the musculoskeletal system, including muscles, ligaments, tendons, joints and bones. Musculoskeletal disorders are one of the most common health problems experienced by workers. The purpose of this study was to find the relationship between work duration and musculoskeletal disorders in security officers at FKIK Krida Wacana Christian University. The research data was obtained using a respondent data questionnaire and a Nordic Body Map on 32 samples at the FKIK Krida Wacana Christian University. Based on the results of the age distribution, the majority of research subjects were >30 years old and male. Most of the respondents experienced musculoskeletal disorders in at least one part of the body and the rest had no complaints at all. The distribution of work duration variable on musculoskeletal disorders in the study subjects showed that most worked for 8 hours/day with a longer total duration of rest but still experienced complaints on the skeletal muscles. Based on the results of the Chi-Square analysis test, a p value of 1.000 was obtained, which means that there is no significant relationship between length of work and musculoskeletal disorders. This is influenced by individual factors smoking habits of the respondents.